Analysis of Regional Development Planning Strategies In Central Kalimantan To Improve Community Welfare - Dedi Takari; Yully Liani (Pelopor Publikasi Akademika, 2025)
Central Kalimantan Province has great potential in the agriculture, forestry, and mining sectors, but its management still faces various challenges such as limited infrastructure, low quality of human resources, and environmental damage. This study aims to analyze regional development strategies through a SWOT analysis approach to improve community welfare. The results of the analysis show that the potential of rich natural resources and strategic geographical position are the main strengths, while the limited infrastructure and access to public services are significant weaknesses. Investment opportunities and government support can be leveraged to accelerate development, but challenges such as environmental degradation and social conflicts must be managed effectively. Strategy recommendations include infrastructure development, human resource capacity building, and sustainable management of natural resources. Comprehensive implementation and multi-stakeholder collaboration are needed to make Central Kalimantan a developed and prosperous region.